ISLAMIC VALUES IN INCLUSION LEARNING MANAGEMENT IN SCHOOL OF LIFE LEBAH PUTIH SALATIGA - Nuridin, Nuridin; Jupriyanto, Jupriyanto; Indraswari, Elvrida Rosalia (Pascasarjana IAIN Kudus, 2019)
The aim of this study is to describe: (1) planning (2) organizing; (3) implementation: and (4) inclusive learning assessment system at the Salatiga White Bee School of Life. This research uses a qualitative approach. The research subjects were the Principal and facilitator. Data collection techniques used semi-structured interviews, participatory observation, and documentation studies which were then analyzed by data reduction, data display, and drawing data conclusions. Based on the results of the study it can be concluded that: (1) planning includes; the curriculum used is KTSP with some modifications, facilitators, and school consultants are involved in setting learning plans; (2) organization includes; organizing learning layouts, learning resources, and methods and media in learning, (3) implementation includes; development of life skills and finding identities, prioritizing enjoyable learning, and facilitators who help ABK, and (4) the assessment system includes; authentic appraisers, and report cards for ABK.